2013
DOI: 10.1111/pbi.12119
|View full text |Cite
|
Sign up to set email alerts
|

The production of recombinant cationic α‐helical antimicrobial peptides in plant cells induces the formation of protein bodies derived from the endoplasmic reticulum

Abstract: Summary Synthetic linear antimicrobial peptides with cationic α‐helical structures, such as BP100, are valuable as novel therapeutics and preservatives. However, they tend to be toxic when expressed at high levels as recombinant peptides in plants, and they can be difficult to detect and isolate from complex plant tissues because they are strongly cationic and display low extinction coefficient and extremely limited immunogenicity. We therefore expressed BP100 with a C‐terminal tag which preserved its antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…The sequences encoding BP100.2 [7], BP100-DsRed-tag54 and DsRed-tag54 [8] were subcloned into these plasmids using the Spe I and BamH I restriction sites.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sequences encoding BP100.2 [7], BP100-DsRed-tag54 and DsRed-tag54 [8] were subcloned into these plasmids using the Spe I and BamH I restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…Plant expression of recombinant cationic α-helical peptides such as BP100 is preferable for industrial and phytosanitary applications. We have recently showed that active BP100-derived peptides can be expressed as recombinant peptides in plants [7], [8], demonstrated by the increased resistance of GM plants to some rice pathogens [7] and by in vitro growth inhibition assays [8]. These recombinant BP100-derived peptides include endoplasmic reticulum (ER) retention motifs to minimize toxicity to the host plant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific challenges for the biotechnological production of short AMPs in cell factories are their small length, susceptibility to degradation, and potential toxicity to the producer host. Fusion to other protein motifs has been used to stabilize AMP in the producer host (Company et al 2014;Viana et al 2013;Wang et al 2014) or to target AMP to cell compartments such as the endoplasmic reticulum (ER) or protein bodies (Bundó et al 2014;Coca et al 2006;Company et al 2014) where they can accumulate in high amounts.…”
Section: Introductionmentioning
confidence: 99%